2008
DOI: 10.1136/jech.2006.058768
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful differences in maternal smoking behaviour during pregnancy: implications for infant behavioural vulnerability

Abstract: Pathways from pregnancy smoking to offspring behaviour are complex and multi-determined. These findings suggest that both exposure and maternal characteristics associated with pregnancy smoking status contribute to offspring behavioural patterns. Research that characterises differences between quitters and persistent smokers and examines the role of these differences in prediction of early vulnerabilities and problems in adaptation over time will be important for elucidating these pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 34 publications
(43 reference statements)
8
44
0
Order By: Relevance
“…Current smokers entering our cohort were significantly younger, less educated and from lower socioeconomic backgrounds than recent ex-smokers. These findings are similar to those from previous UK cohorts, which reported that women who smoke before or during pregnancy are more likely to be less than 25 years of age,10 12 more likely to have left education at a younger age and gained fewer formal qualifications,10 13 36 37 and to be from lower socioeconomic groups than non-smokers 10–13 36 37…”
Section: Discussionsupporting
confidence: 90%
“…Current smokers entering our cohort were significantly younger, less educated and from lower socioeconomic backgrounds than recent ex-smokers. These findings are similar to those from previous UK cohorts, which reported that women who smoke before or during pregnancy are more likely to be less than 25 years of age,10 12 more likely to have left education at a younger age and gained fewer formal qualifications,10 13 36 37 and to be from lower socioeconomic groups than non-smokers 10–13 36 37…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the association between cigarette smoking and psychiatric disorders in general has been documented (e.g., Degenhardt & Hall, 2001;Kahler et al, 2009 ;Saban & Flisher, 2010) and lends support to the interpretation that smoking in pregnancy, a risky behavior likely to affect infant health, may be a marker for psychological distress in mothers, particularly for those who smoke more heavily. This interpretation is consistent with but more focused than the suggestion by Pickett et al (2008) that smoking in pregnancy may be a marker for psychosocial difficulties of these mothers or that of Hutchinson, Pickett, Green, and Wakschlag (2010) that it may be a marker for "intergenerational processes associated with both the tendency to smoke and to have offspring with behavioural and cognitive problems . .…”
Section: Discussionsupporting
confidence: 80%
“…When indicators of SES are examined, results show that women who smoke in pregnancy are more likely to be from low-income families, to be less well educated, and to live in less-advantaged neighborhoods (e.g., Higgins et al, 2009;Kandel, Griesler, & Schaffran, 2009;Maughan et al, 2004;Pickett et al, 2008;Sellstrom, Arnoldsson, Bremberg, & Hjern, 2008;Weaver, Campbell, Mermelstein, & Wakschlag, 2008 ). Some studies also show that pregnancy smokers are more likely to be single (Flick et al, 2006;Pickett et al, 2008;Sellstrom et al, 2008;Wakschlag et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RITQ is also used in many large-scale longitudinal studies such as the Millennium Cohort Study (Pickett, Wood, Adamson, DeSouza, & Wakschlag, 2008), the National Institute of Child Health and Human Development Study of Early Child Care (Bradley & Corwyn, 2008), and the Helsinki Longitudinal Temperament Study (Martin, Wisenbaker, Baker, & Huttunen, 1997). Longitudinal studies have provided evidence that temperament is associated with later development of mental disorder (Lewis & Olsson, 2011;Sayal, Heron, Maughan, Rowe, & Ramchandani, 2013), behavioral problems (Prior, Sanson, Smart, & Oberklaid, 2000), as well as cognitive (Maziade, Côté, Boutin, & Bernier, 1987), language (Taylor, Christensen, Lawrence, Mitrou, & Zubrick, 2013), and academic performance outcomes (Saudino & Plomin, 2007).…”
Section: Introductionmentioning
confidence: 99%